ANALISIS STUDI KOMPARATIF TENTANG PENERAPAN TRADISIONAL COSTING CONCEPT DENGAN ACTIVITY BASED COSTING (STUDI KASUS PADA RUMAH SAKIT SILOAM DI MANADO) - Sumendap, Olivia H.S.; Saerang, David Paul Elia; Pangemanan, Sifrid Sonny (Universitas Sam Ratulangi, 2013)
This research compared the traditional method of cost calculation with activity based costing (ABC) in determining the inpatient room rate at Siloam Hospital. This research uses descriptive analytical method. Data obtained by analyzing documents, participant observation, interviews with chief accounting company then comparated with the existing literature. Implementation of activity based costing (ABC) provides an excellent effect in improving efficiency and resource activities. Calculation of costs with ABC is able to produce cheaper and more accurate when compared with traditional approaches. In the end Siloam Hospital is able to provide affordable rates for patients.